KARAKTERISTIK HIDROLOGI DAN DAMPAKNYA TERHADAP BANJIR DAERAH ALIRAN SUNGAI JAMBO AYE DI ACEH INDONESIA (Hydrological Characteristics And Its Impact On Flood Jambo Aye Basin In Aceh Indonesia) - Cut Azizah; Hidayat Pawitan; Nuraida Nuraida; Halus Satriawan; Rahmat Abbas; Sarif Robo; Misnawati Misnawati (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2021)
ABSTRACT The increase in damage are experienced by many watershed due to human interactions and interventions which impacted in the hydrological balance that may lead to disasters. Flooding is a routine hydrological disaster that occurs in the Jambo Aye Basin. This study aims to analyze the relationship of the hydrological characteristics of the Jambo Aye Basin to the potential and occurrence of floods. Characteristics of slope, soil movement, hydrological soil group (HSG) analysis, antecedent precipitation index (API) and runoff curves are used as hydrological indicators to identify potential flooding in the watershed. The analysis show that the Jambo Aye Basin is proned to flooding. The potential for inundation floods is found in the downstream area which has the characteristics of gentle slopes (12%), very low infiltration capacity (37,95%), high runoff curve values (17%) and high levels of wetness (26%). Flash floods have the potential to occur in the upstream area which has the characteristics of steep slopes, soil movement and high rainfall. Integrated watershed management needs to be carried out in the Jambo Aye Basin considering the frequent occurrence of floods. Keywords: antecedent precipitation index; flash floods; flood; curve numbers; land use ABSTRAKDaerah Aliran Sungai (DAS) mengalami peningkatan kerusakan akibat hubungan dan interferensi manusia yang berdampak pada kesetimbangan hidrologi sehingga terjadi bencana. Bencana banjir yang merupakan bencana hidrologi rutin terjadi di DAS Jambo Aye. Penelitian ini bertujuan untuk menganalisa hubungan karakteristik hidrologi DAS Jambo Aye terhadap potensi dan kejadian banjir di wilayah DAS Jambo Aye. Karakeristik kemiringan lereng, pergerakan tanah, analisis kelompok hidrologi tanah (HSG), Antecedent Precipitation Index (API) dan kurva limpasan digunakan sebagai indikator hidrologi untuk mengidentifikasi potensi banjir yang terjadi di DAS Jambo Aye. Analisis menunjukkan DAS Jambo Aye termasuk wilayah yang berpotensi mengalami banjir. Potensi banjir genangan terdapat di wilayah hilir yang mempunyai karakteristik lereng landai (12%), kapasitas infiltrasi sangat lambat (37,95%), nilai kurva limpasan tinggi (17%) dan tingkat kebasahan yang tinggi (26%). Banjir bandang berpotensi terjadi di wilayah hulu yang mempunyai karakteristik lereng curam, adanya pergerakan tanah dan curah hujan yang tinggi. Pengelolaan DAS perlu dilakukan di DAS Jambo Aye mengingat kejadian banjir yang sering terjadi. Kata kunci: antecedent precipitation index; banjir bandang; banjir; curve number; penggunaan lahan